Modelagem numérica na estimativa do impacto da Coroa do Quiriri na hidrodinâmica do rio Pará, Brasil - MONTEIRO, Giulian Smith Araújo (2019)
The amazon estuaries are of the utmost importance for its region for providing water and food for the fauna and population, also being a mean of flow of products destinated to the exportation. However, the hydrodynamics of estuaries such as Para River is complex and some points of its channel, such as submerged sandbars, represent danger to large vessels. In this estuary, the sandbar popularly known as Quiriri Crown is located on its mixture zone and this study aims to verify the impacts, on hydrodynamics, that the removal of Quiriri Crown could bring to the Para River estuary. With this objective, the bidimensional modelling of the region was done through the software Delft 3D. Using bathymetric and hydrodynamic data, two scenarios were made for the simulations, being the first one the real stage and the second with the Quiriri Crown removed. From the validation, was obtained R²=0.8447, RMSE =0.3069 and ρ=0.9323 for the water level data in the upper estuary, R²=0.8585 and ρ=0.9011 for velocity data and R²=0.9353 and ρ=0.9451 for instantaneous discharge data. On the comparison between simulations, it became clear that the removal of Quiriri Crown reduced the influence of the tidal prism in the estuary, indicating that the Quiriri Crown boosts the tide signal in Para River by reducing the area of the main channel in the estuary mouth. From the model data, it can be inferred that the significant changes observed on the Para River hydrodynamics may strike other oceanographic parameters, however, it’s necessary the addition of data about these parameters to the model in order to fully access the changes on the estuary caused by the Quiriri Crown removal.